Development of A Canva-Based Interactive E-Module in Arabic Language Learning on The Topic of Al-Sa'ah at MTsN 2 Sinjai - Nurhikmah Rahing; Hamka Ilyas; Azizul Hakim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aims to analyze student’s needs for interactive e-module teaching materials based on Canva in the Arabic language subject focusing on the topic of al-sa’ah for Grade VIII at MTsN 2 Sinjai, describe the development procedures of Canva-based interactive e-module teaching materials, and assess the validity and practicality of these teaching materials. This study is a type of research and development (R&D) designed to produce Canva-based interactive e-modules. The research design employs the 4D model by Thiagarajan, Semmel, and Semmel, which includes the stages of define, design, develop, and disseminate. The results of the research and development consist of a needs analysis showing the demand for Canva-based interactive e-modules. The validity analysis of the developed e-module falls into the